PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN YANG TERGABUNG DI JAKARTA ISLAMIC INDEX (JII) - Febriani, Juliana; Hambali, Denny (Jurnal Nusa Akuntansi, 2025)
This study aim to analyze the effect of profitabily, liquiditas, leverage and solvability on firm value. This research was conducted on companies that are members of the Jakarta Islamic Index and listed on the Indonesia stock exchange, using a sample size of 11 companies. Data obtained by visiting the website of each company. The data analysis technique used is in the form of classical assumption test analysis, multiple liniear analysis and is equipped with hypothesis testing. The results of this study indicate that the profitability of liquidity leverage and solvability have a positive effect on firm value